2011
DOI: 10.1049/el.2011.0335
|View full text |Cite
|
Sign up to set email alerts
|

V th compensated AMOLED pixel employing dual-gate TFT driver

Abstract: A simple active-matrix organic light-emitting diode (AMOLED) pixel with conventional voltage driving and ability to compensate for the V th shift of thin-film transistors (TFTs) is proposed. The stable pixel operation is achieved by the employment of a dual-gate TFT for OLED driving. Simulation results also show that a new pixel exhibits almost linear programming I -V characteristics, whereas a conventional pixel design features a highly nonlinear behaviour.Introduction: Displays with active-matrix organic lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…These transfer curves exhibit parallel shifts at different V TG values. Those phenomena are attributed to the attraction and expelling of free carriers in the active layer by the top gate, which is well explained in [6]. It provides a way of using the bottom gate of the dual-gate a-IGZO TFT as the primary gate while controlling the top gate independently.…”
Section: Device Fabrication and Characteristicsmentioning
confidence: 89%
See 1 more Smart Citation
“…These transfer curves exhibit parallel shifts at different V TG values. Those phenomena are attributed to the attraction and expelling of free carriers in the active layer by the top gate, which is well explained in [6]. It provides a way of using the bottom gate of the dual-gate a-IGZO TFT as the primary gate while controlling the top gate independently.…”
Section: Device Fabrication and Characteristicsmentioning
confidence: 89%
“…Taking advantage of the fact that the threshold voltage V th of the dual-gate a-IGZO TFT can be shifted by the top gate of the TFT [5], [6], we are able to design the circuit with more flexibility. In fact, some new circuits utilizing the dual-gate TFTs were proposed [3], [7]- [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, they have some drawbacks such as the current driving scheme [17], the need of both n and p type TFTs [18], individual driving of the anode and the cathode of OLED [19], or indirect voltage driving through capacitive coupling [20]. Taking the advantage of the fact that the Vth of dual-gate amorphous InGaZnO4 (a-IGZO) TFT can be controlled by the second gate of the TFT [21][22], N.D. Jankovic and V. Brajovic et al proposed a pixel circuit [23], but it is based on a premise that the effect of the second gate on the Vth of the dual-gate TFT is constant, which is not necessarily true.…”
Section: Objective and Backgroundmentioning
confidence: 99%
“…1(a)). Jankovic et al has suggested simple a 2T1C (two TFTs and one capacitor) circuit but, optimum design is needed to get appropriate performance of compensation [12]. Tai et al has also implemented using simple 3T2C circuit, which uses top (auxiliary)-gate sweep to extract V TH of TFT for compensation.…”
Section: Introductionmentioning
confidence: 99%